2014
DOI: 10.1080/13811118.2014.996693
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physicians’ and Nurses’ Recent Suicide Attempts: An Exploratory Study

Abstract: Aim: To examine the characteristics of physicians' and nurses' suicide attempts (SA).Method: A retrospective review of 493 medical records of physicians and nurses admitted to an inpatient unit for health professionals; 36 patients had a recent SA.Results: Depression, cluster B and C personality disorders, and a history of previous SA were more prevalent in patients with a recent SA compared to those without it. Both professional groups preferred drug overdose as a suicide method. Physicians made more lethal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
2
16
0
4
Order By: Relevance
“…Interventions that created a people-focused working culture that recognised this important link between doctors' and patients' health and well-being, balanced positive and negative performance and promoted doctors' learning from both. In addition, acknowledging the positive and negative aspects of a medical career helped doctors to thrive at work and deal with work pressures (this was demonstrated in context-mechanism-outcome configurations [12][13][14][15]. Finally, we found that the way that interventions were implemented was critically important.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Interventions that created a people-focused working culture that recognised this important link between doctors' and patients' health and well-being, balanced positive and negative performance and promoted doctors' learning from both. In addition, acknowledging the positive and negative aspects of a medical career helped doctors to thrive at work and deal with work pressures (this was demonstrated in context-mechanism-outcome configurations [12][13][14][15]. Finally, we found that the way that interventions were implemented was critically important.…”
Section: Resultsmentioning
confidence: 92%
“…11 In the UK, the mental health of the NHS workforce, including that of doctors, is of great concern. [12][13][14][15][16] In 2015, the Head of Thought Leadership at The King's Fund declared that stress levels among NHS staff are 'astonishingly high' and need to be treated as 'public health problem'. 17 In the 2018 NHS staff survey, 39.8% of respondents indicated that they had been unwell in the previous 12 months because of work-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Some GPs in this study who recognised the importance of their symptoms were, however, prompted by this to seek help. Given the high rates of suicide among doctors in general and GPs in particular, 9 it is imperative that UK GPs are given the support they need so that they can access appropriate help before they reach this crisis point.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…6,7 Additional pressures for GPs in the UK come from sources such as the Quality and Outcomes Framework (QOF) and the implications of future cuts in NHS funding. 6 Reports of GPs feeling dissatisfied, 6 distressed, anxious, 7,8 and suicidal 9 are rising. Some GPs report misuse of substances, 7 while others feel exhausted, 'grumpy', and have feelings of hatred towards their work.…”
Section: Introductionmentioning
confidence: 99%
“…Las anfetaminas hasta un 10% y la cocaína entre un 3% y un 5% Como el resto de colectivo médico, los residentes presentan dificultades a la hora de pedir ayuda cuando sufren un trastorno mental. Estas dificultades son incluso mayores si han desarrollado una adicción (Braquehais et al, 2016). A la cultura de invulnerabilidad asociada al ejercicio de la Medicina, inculcada desde el pregrado, se suma también el estigma asociado al padecimiento mental o emocional, mayor aún, si cabe, entre los profesionales de la salud.…”
unclassified